Solitary fibular metastasis from lung adenocarcinoma with gene mutation: a case report - Chen, Jiechen; Alkhatatbeh, Ahmad; Lin, Yinbing; Lu, Xiaolin; Chen, Bin; Chen, Hongjiang; Lu, Xiaohui; Wu, Hansheng; Hu, Jun (Frontiers in Oncology, 2025)
Solitary fibular metastasis from lung adenocarcinoma is exceedingly rare, with only five documented cases. This report presents a 40-year-old non-smoking Asian male who initially presented with painful swelling in the right knee. Imaging revealed bony destruction of the right fibular head, and further investigations with chest CT, PET/C, pathologic biopsy and genetic testing identified a primary lung adenocarcinoma with EGFR exon 19 deletion mutation. The patient was treated with Osimertinib, resulting in significant tumor reduction. This was followed by thoracoscopic lobectomy and systematic lymph node dissection, and local radiotherapy for the fibular metastasis. The patient experienced complete pain relief and showed no recurrence or metastasis over a 26-month follow-up. This case highlights the diagnostic challenge posed by atypical presentations of metastasis and underscores the importance of comprehensive evaluation, adherence to treatment guidelines, and a multidisciplinary approach in managing oncological patients. The successful outcome in this young patient emphasizes the effectiveness of personalized treatment strategies in optimizing patient prognosis, offering valuable insights for similar clinical scenarios.